Hypoxia-inducible Factor-1α directs renal regeneration induced by decellularized scaffolds. (May 2018) - Yu, Yaling; Cui, Haomin; Chen, Chuan; Wen, Gen; Xu, Jia; Zheng, Binbin; Zhang, Jianse; Wang, Chunyang; Chai, Yimin; Mei, Jin
Abstract: Although mammalian kidney regeneration has been reported to occur throughout life, mature kidneys in mammals are not thought to regenerate sufficiently, particularly glomeruli. In our previous work, we found that renal regeneration could be enhanced by decellularized renal scaffolds after partial nephrectomy. In this study, we verified that the enhanced renal regeneration mediated by decellularized scaffolds could be attributed to regenerated glomeruli, which were counted both indirectly and directly under a microscope. Using the isobaric tag for relative and absolute quantitation, we performed proteomics analysis and found that hypoxia-inducible factor (HIF)-1α may be a key factor involved in induced renal regeneration. Dimethyloxyallyl glycine (DMOG), a propyl hydroxylase inhibitor, was applied to stabilize constitutive expression of HIF-1α protein, and small interfering RNA was used to inhibit gene expression. Administration of DMOG to decellularized scaffold-grafted rats improved the induced renal regeneration, whereas si Hif1α transfection decreased the regeneration capacity. These findings revealed the critical role of HIF-1α in renal regeneration and provided important insights into our understanding of kidney development and the treatment of various kidney diseases.